Exploring the Role of Nutrition and Physiology in Basketball Performance : A Literature Review - Muhamad Ramos; Ronni Yenes; Eri Barlian; Hendri Neldi; Yovhandra Ockta (Jurnal Penelitian Pendidikan IPA, 2024)
Basketball is a high-intensity sport that requires exceptional physical performance, including strength, speed, and endurance. Beyond technical skills, physiological factors such as nutrition play a crucial role in optimizing performance. Articles were sourced from Scopus, PubMed, and Google Scholar, using keywords such as "nutrition," "physiology," "basketball performance," and "athlete performance." The findings highlight the importance of tailored nutrition plans and the need for ongoing education in sports nutrition to support the physiological demands of basketball. Proper nutrition supports muscle strength, endurance, and recovery after intense training or competition. This literature review explores the relationship between nutrition, physiology, and basketball performance. Key macronutrients like carbohydrates, proteins, and fats are essential for energy, muscle repair, and recovery, while micronutrients such as B vitamins, calcium, and magnesium contribute to overall health and performance. Maintaining fluid balance and electrolytes is vital to prevent performance decline, given the high intensity of the game. Physiological factors like body composition, aerobic capacity, and metabolism influence how the body utilizes nutrients during play. Moreover, adequate nutrition knowledge among athletes and coaches is essential to maximize performance and minimize injury risk. This review aims to synthesize current research findings to provide evidence-based nutritional strategies and physiological insights that can improve endurance, enhance performance, and support recovery in basketball players